Internal jugular vein duplication-incidental finding: a rare case report - Vinchurkar, Kumar M.; Gupta, Ankit; Patil, Rashmi S.; ., Shekhargouda; Garg, Akanksha (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Internal jugular vein duplication (IJVD) during neck dissection is a rare finding, with a 4/1000 incidence recorded in unilateral neck dissections. An intra-operative unilateral IJVD was identified as an unexpected finding in a 49-year-old gentleman who underwent surgery for upper gingivobuccal sulcus carcinoma. In case IJVD is present then high chances of injury to anterior compartment in early steps of neck dissection as it is present anterior and medial to Sternocleidomastoid muscle (SCM), while chances of injury to posterior compartment when addressing level II, III, and IV neck nodes. Though duplication has no physiological significance, it has clinical implications during interventional, surgical and other procedures, so detailed knowledge of this variation in anatomy helps in preventing untoward injury or misinterpretation. To understand the variation in anatomy, it is important to document the findings of this anomaly. Objective of case report is to explain the presentation of internal jugular vein duplication, its clinical consequences and to discuss literature present pertaining to its embryology.